Analisa Pengiriman Barang di PT Indofood Sukses Makmur Bogasari Flour Mills - Malvin Adi Masta; Prayonne Adi (Jurnal Titra, 2018)
One of the issues of corporate refinement is to improve customer service by reducing the loss of shipment goods. This problem is caused by three factors namely the warehouse in Surabaya, transporter, and end customers. During the loading process in warehouses in Surabaya, the loading worker are required to make a report that will highlight the quantity tally. One of the methods used to analyze the problem is the FMEA method. The FMEA method is categorized into three phases, i.e. identification of problems, assessment of the results of identification and determination of repair problems. The results of the FMEA method evaluation will be used as a guide for improvement and are expected to help reduce the frequency of loading of goods caused by warehouses in Surabaya.